The Importance of Prenatal Diagnosis for the Early Detection of Fetal Abnormalities in Rural Areas, Indonesia: A Mixed-Method Study - Supriyatiningsih Wenang; Lidia Febrianti; Riken Nur Diaz; Fajar Hafiz Sandiawan; Diyah Nahdiyati; Franz Bahlmann (IMR Press, 2024)
Background: Prenatal diagnosis in rural areas is a global challenge especially for maternal reproductive health. The challenges of implementing prenatal diagnosis in rural areas include: low public awareness and knowledge, minimal access to health care facilities, low economic factors. Yogyakarta represents Indonesia as a province with the same proportion of urban and rural areas. Apart from that, there is still a culture that influences the knowledge and behavior the health care community. The incidence of congenital abnormalities is increasing in rural areas due to delays in early detection during pregnancy. By using a mixed-method approach, this study aims to provide insight into the importance of prenatal diagnosis for pregnant women in rural areas. Methods: This research is a mixed-method study with 100 webinar participants of community service, 6 health care workers, and 6 pregnant women. Demographic data and knowledge about prenatal diagnosis are presented through quantitative methods. The qualitative data presented through in-depth interviews explored the perspectives of health care workers and pregnant women regarding experiences, obstacles, and support in carrying out prenatal diagnosis. Thematic analysis was used in this study. Results: The importance of knowledge in the early detection of fetal abnormalities and children's growth development has a significance value of 0.000 each (p-value < 0.05). In contrast, the hospital services expectation has 0.243. Qualitative reports indicated that the achievement of prenatal diagnosis services requires awareness of pregnant women and support from health care workers as direct providers of counseling and services. Pregnant women in this study realized the importance of prenatal diagnosis to detect early pregnancy abnormalities. Conclusions: Prenatal diagnosis in rural areas is an effort to increase early detection of fetal abnormalities and improve child development. The implementation of prenatal diagnosis in rural areas is supported by the active role of health workers and non-health workers. Several obstacles to the implementation of prenatal diagnosis in rural areas are the lack of knowledge of pregnant women, fear of poor examination results, distance from the pregnant woman's house to the health care facilities, uneven availability of ultrasound equipment, and high costs of ultrasound examinations. The government can increase access of prenatal diagnosis in rural areas, through free ultrasound subsidies and the implementation of pregnant women's classes in each village.